Tardigrades of the Tree Canopy: Milnesium swansoni sp. nov. (Eutardigrada: Apochela: Milnesiidae) a new species from Kansas, U.S.A. - Young, Alexander; Chappell, Benjamin; Miller, William; Lowman, Margaret (Zootaxa, 2016)
Milnesium swansoni sp. nov. is a new species of Eutardigrada described from the tree canopy in eastern Kansas, USA. This species within the order Apochela, family Milnesiidae, genus Milnesium is distinguished by its smooth cuticle, narrow buccal tube, four peribuccal lamellae, primary claws without accessory points, and a secondary claw configuration of [3-3]-[3-3]. The buccal tube appears to be only half the width of the nominal species Milnesium tardigradum for animals of similar body length. The species adds to the available data for the phylum, and raises questions concerning species distribution.